How should central banks communicate? - Michael Ehrmann; Marcel Fratzscher (European Central Bank (ECB), 2005)
The paper shows that central bank communication is a key determinant of the market's ability to anticipate monetary policy decisions and the future path of interest rates. Comparing communication policies by the Federal Reserve, the Bank of England and the ECB since 1999, we find that communicating the diversity of views among committee members about monetary policy lowers the market's ability to anticipate policy decisions as well as the future path of interest rates. This effect is sizeable, accounting for instance for one third to half of the prediction errors of FOMC policy decisions. By contrast, individualistic communication regarding the economic outlook is found to be beneficial for the Federal Reserve, enabling market participants to better anticipate the future path of interest rates. Thus, it is the collegiality of views on monetary policy but the diversity of views on the economic outlook that enhance the effectiveness of central bank communication.
Keywords: E43; E52; E58; G12; 330; Bank of England; committee; communication; economic outlook; effectiveness; European Central Bank; Federal Reserve; monetary policy; Geldpolitik; Zentralbank; Internationale Zusammenarbeit; EU-Staaten; Großbritannien; USA